Using screencasts in the teaching of modern languages: investigating the use of Jing® in feedback on written assignments. Issue 3 (27th May 2018) - Harper, Felicity; Green, Hannelore; Fernandez-Toro, María
ABSTRACT: Written assessment – in both its senses as assessment of student writing and as written feedback on the task – is an essential part of the learning journey in foreign language learning; and at our distance-learning institution it is one of the main teaching strategies in the communication between tutors and students. In this research project, we investigated how error correction and written feedback could be augmented by adding personalised screencasts to these traditional approaches to teaching through assessment. Students and tutors on Spanish and German modules ranging from Beginners to Upper Intermediate Level participated in evaluating the screencasting software, Jing®, in terms of its clarity, accessibility and affective impact. The data collected includes questionnaire feedback from tutors on their experience of the tool and their opinion of it, questionnaire and interview feedback from students on receiving visual and auditory commentary on their assignments, a comparison between the feedback provided by the same tutors on the same assignment with and without screencasting and a follow-up questionnaire to tutors investigating their current use of screencasting beyond the project. Both students and tutors responded positively to the tool, finding that it enhanced the sense of tutor presence and facilitated communication of the tone of feedback: hearing the tutor's voice explaining the corrections or recommendations for improvement onscreen led to increased affective engagement on the part of the student. Explanations were found to be clear and memorable.